Relationship Analysis Between Leaf-Stomata Characteristics with Cocoa Resistance to Vascular-Streak Dieback - Agung Wahyu Soesilo; Poppy Arisandy; Indah Anita Sari; Rudi Harimurti (Indonesian Coffee and Cocoa Research Institute, 2016)
Characteristics of leaf-stomata indicate having relationship with the resistance of cocoa to vascular-streak dieback (VSD) caused by Ceratobasidum theobromae. This research has objective to identify the relationship between leaf-stomata haracteristicsto VSD resistance in order to develop criteria for selection. Trial was establised in randomized-complete block design with three blocks as replications in Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute (ICCRI) using 15 clones which had different background on VSD resistance. Leaf-stomata of the tested clones were characterized using variables of number of stomata, stomata size, width of opened-stomata and size of stomata mouth in three different level of leaf growth, namely flush, young and mature. VSD resistance was assessed by scoring the damage in the scale of 0-6 that the tested clones were classified into five group sof resistance. Analysis of variance indicated a significant effect of cocoa clone to the number of stomata in all categories of leaf sample but the other leaf-stomata haracteristics were significantly affected by cocoa clone just at the young and mature leaf. Correlation analysis performed a significant inter-correlation between variables of leaf-stomata characteristics in young leaf and the score of VSD resistance. However, number of stomata and width of opened-stomata in the mature leaf were significantly correlated to the score of VSD resistance. Genetic variance analysis showed a high category of broad sense heritability for the number of stomata and width of the penedstomata in young leaf that both of the variables can be developed as criteria for selection on VSD resistance.